Cryo-imaging of photosystems and phycobilisomes in Anabaena sp. PCC 7120 cells - Steinbach, Gábor; Schubert, Félix; Kaňa, Radek (Journal of photochemistry and photobiology. B, Biology, 2015)
Primary photosynthetic reactions take place inside thylakoid membrane where light-to-chemical energy conversion is catalyzed by two pigment-protein complexes, photosystem I (PSI) and photosystem II (PSII). Light absorption in cyanobacteria is increased by pigment-protein supercomplexes--phycobilisomes (PBSs) situated on thylakoid membrane surfaces that transfer excitation energy into both photosystems. We have explored the localization of PSI, PSII and PBSs in thylakoid membrane of native cyanobacteria cell Anabaena sp. 7120 by means of cryogenic confocal microscopy. We have adapted a conventional temperature controlling stage to an Olympus FV1000 confocal microscope. The presence of red shifted emission of chlorophylls from PSI has been confirmed by spectral measurements. Confocal fluorescence images of PSI (in a spectral range 710-750 nm), PSII (in a spectral range 690-705 nm) and PBSs (in a spectral range 650-680 nm) were recorded at low temperature. Co-localization of images showed spatial heterogeneity of PSI, PSII and PBSs over the thylakoid membrane, and three dominant areas were identified: PSI-PSII-PBS supercomplex area, PSII-PBS supercomplex area and PSI area. The observed results were discussed with regard to light-harvesting regulation in cyanobacteria.
Keywords: Photosystem I Protein Complex; Cyanobacteria; konfokální mikroskopie; Cryogenic microscopy; Photosynthesis; Membrane domains; Anabaena; Confocal microscopy; fotosystém I (proteinový komplex); molekulární modely; Microscopy, Confocal; Models, Molecular; konformace proteinů; Phycobilisomes; Photosystem II Protein Complex; Protein Transport; Protein Conformation; fykobilizomy; transport proteinů; fotosystém II (proteinový komplex)